Artificial neural network for landslide vulnerability mapping in Leitimur Peninsula Ambon Island - Puturuhu, Ferad; Danoedoro, Projo; Sartohadi, Junun; Srihadmoko, Danang (2022)
Artificial neural network (ANN) has been widely used in remote sensing to classify the various types of data. Moreover, it provides better accuracy results than statistical methods. In this study, AAN was applied to map landslide vulnerability zone in Leitimur Peninsula Ambon where landslide has frequently occurred in the period 2012 until now resulting in losses to community. The objective of this study was to determine the landslide vulnerability level zones of the study area. The method used was the logistic regression and ANN. The results showed that the largest zone (9957.33ha) or 65.47% of the study area is in low landslide vulnerability level, while the best result of the accuracy test is the ANN analysis with the value of 72.55%.